STUDENTS’ PERCEPTION ON THE EFFECTIVENESS OF ONLINE-BASED LEARNING (BY USING GOOGLE CLASSROOM APPLICATION) - Kerenhapuk Rejoice Trivena Golung; Nihta Liando; Maikel Sanger (Program Studi Pendidikan Bahasa Inggris, 2023)
E-learning in academics which is characterized by the use of multimedia constructs made the process of learning more active, interesting, and enjoyable This study aims to describe students' perceptions about the effectiveness of using the Google Classroom application in learning activities on the eight grade students of SMP Negeri 4 Tondano in the academic year 2021-2022. In conducting this research, researchers used a questionnaire as a medium for collecting data. Researchers analyzed the data in 4 factors such as usefulness, ease of use, ease of learning and satisfaction. Usefulness refers to whether the application is useful and helps learning activities every day. Ease of use relates to the ease of the user in running the application. Ease of learning relates to the ease of users in learning to use applications. And satisfication refers to user satisfaction with the Google Classroom application. Based on the data, the researcher concluded that Google Classroom application is effective to use as a learning medium.